Women Transcending in Lucy Maud Montgomery’s Anne of Green Gables - Ule, Maria; Sari, Dian Eka (STBA Prayoga Padang, 2025)
This research explored the representation of women's transcendence in Lucy Maud Montgomery's Anne of Green Gables. In the 20th century, life in Green Gables was characterized by traditional values and strict gender expectations. Thus, this research examined the causes that trigger women from Green Gables to engage in transcendence and the results of their struggles. Using a qualitative method, data were collected from novels, articles, and other literary sources. Through a Beauvoirian lens, this research explored how women negotiate their roles and identities in the context of patriarchal norms and structures. It provided an insight into women's achievements in transcending roles and identities. The findings revealed two causes triggering Green Gables Women to transcend: discrimination and pressure. Besides, there were two ways women do while transcending: creativity and independence. Lastly, the result of women transcending; economic independence and freedom of speech.